An in vitro comparison of nickel and chromium release from brackets - Ana Cristina Soares Santos Haddad; Andre Tortamano; Alexandre Luís de Souza; Pedro Vitoriano de Oliveira (Sociedade Brasileira de Pesquisa Odontológica, 2009)
This study aimed at comparing amounts of nickel (Ni) and chromium (Cr) released from brackets from different manufacturers in simulated oral environments. 280 brackets were equally divided into 7 groups according to manufacturer. 6 groups of brackets were stainless steel, and 1 group of brackets was made of a cobalt-chromium alloy with low Ni content (0.5%). International standard ISO 10271/2001 was applied to provide test methods. Each bracket was immersed in 0.5 ml of synthetic saliva (SS) or artificial plaque fluid (PF) over a period of 28 days at 37ºC. Solutions were replaced every 7 days, and were analyzed by spectrometry. The Kruskal-Wallis test was applied. Amounts of Ni release in SS (µg L-1 per week) varied between groups from "bellow detection limits" to 694, and from 49 to 5,948.5 in PF. The group of brackets made of cobalt-chromium alloy, with the least nickel content, did not release the least amounts of Ni. Amounts of Cr detected in SS and in PF (µg L-1 per week) were from 1 to 10.4 and from 50.5 to 8,225, respectively. It was therefore concluded that brackets from different manufacturers present different corrosion behavior. Further studies are necessary to determine clinical implications of the findings.